2019
DOI: 10.12659/msmbr.916258
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Progranulin in a Rat Model of Acute Myocardial Ischemia/Reperfusion are Mediated by Activation of the P13K/Akt Signaling Pathway

Abstract: BackgroundProgranulin is an adipokine, encoded by the progranulin (GRN) gene. Progranulin is expressed in atherosclerosis, but its effects in cardiac ischemia and reperfusion injury are unknown. Therefore, this study aimed to investigate the effects of progranulin in a rat model of acute myocardial ischemia/reperfusion (MI/R) injury in vivo.Material/MethodsThe model of acute MI/R injury was established in male Wistar rats by ligation of the left anterior descending (LAD) coronary artery for 30 minutes and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The PI3K-Akt signaling pathway is enriched in both DAVID and WEAT KEGG analyses. Previous studies have shown that the activation of the P13K/Akt signaling pathway enhances the cardioprotective effect of progranulin in the rat model of acute MI/R injury [ 37 ]. In our study, several genes ( DDIT4 , MYC , CSF3 , TNC , EIF4E1B , PCK2 , and BDNF ) belonging to the P13K/Akt signaling pathway were downregulated in ICM, indicating the potential diagnostic and therapeutic targets of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway is enriched in both DAVID and WEAT KEGG analyses. Previous studies have shown that the activation of the P13K/Akt signaling pathway enhances the cardioprotective effect of progranulin in the rat model of acute MI/R injury [ 37 ]. In our study, several genes ( DDIT4 , MYC , CSF3 , TNC , EIF4E1B , PCK2 , and BDNF ) belonging to the P13K/Akt signaling pathway were downregulated in ICM, indicating the potential diagnostic and therapeutic targets of ICM.…”
Section: Discussionmentioning
confidence: 99%
“…Initial injury provoked by MI associates with subsequent cardiac dysfunction and high mortality 39,40 . A recent study has reported that www.nature.com/scientificreports/ administration of recombinant human progranulin significantly improved cardiac function through activation of PI3K/Akt signaling pathway, 30 min after ischemia followed by 60 min reperfusion in rats 18 . Therefore, in our study, protective effects of progranulin on myocardial I/R injury might be associated with initial activation of PI3K/Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Progranulin gene mutations have been identified in the pathogenesis of frontotemporal lobar degeneration associated with the accumulation of TAR DNA-binding protein 43 (TDP-43) 17 . Previous reports have shown that progranulin protects against I/R injury in the heart, brain and kidney 18 20 . In our previous report, the administration of recombinant progranulin also attenuated neuronal injury by inhibiting neutrophil recruitment in a focal cerebral I/R injury murine model 19 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Phosphoinositide-3 kinase (PI3K) is a key regulator of serine/threonine kinase (Akt) [81] , which in turn downregulate the expression of IκB (Figure 2) [82] . A variety of molecules, including TRIM59 [83] , flavonoids [84] , SH2B1 [85] , progranulin [86] , epigallocatechin [87] , gypenoside [88] , and berberine [89] , have been shown to attenuate inflammation in MI/RI via activating the PI3K/Akt signaling pathway. Studies have implicated the PI3K/Akt signaling pathway in the anti-inflammatory effects of baicalin [90] and 6-gingerol [91] in MI/RI.…”
Section: Introductionmentioning
confidence: 99%